An empirical analysis of firms' performance determinants : a case of Malaysian consumer product companies / Sarah Amirah Ibrahim - Ibrahim, Sarah Amirah (2015)
This paper is to examine the determinants of Malaysian Consumer Product performance in relation to 30 listed consumer product companies. The dependent variable is a return on equity and the independent variable are dividend, debt and tangibility. It will be measure by the year of 2005 until 2010. The quarterly year will be use as to run the data.